2013
DOI: 10.1063/1.4824363
|View full text |Cite
|
Sign up to set email alerts
|

Doped zinc oxide window layers for dye sensitized solar cells

Abstract: The present paper reports the fabrication of dye sensitized solar cell (DSSC), where boron doped ZnO (BZO) and aluminum-boron co-doped ZnO (AZB) thin films were used as front window electrodes. The highly crystalline zinc oxide (ZnO) nanoparticles (NPs) synthesized by the sol-gel route were used as host material for the dye. The efficiencies of the DSSCs formed using the BZO and AZB as window layers were obtained to be 1.56 and 1.84%, respectively. The enhanced efficiency in the case of an AZB window layer bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 46 publications
0
39
1
2
Order By: Relevance
“…Boron doped ZnO for use in DSSC synthesized via solegel technique has been reported in Ref. [19]. In this work, we have introduced a new technique of boron doping into ZnO nanotubes that is adding H 3 BO 3 in a growth solution containing Zn(NO 3 ) 2 and HMT.…”
Section: Introductionmentioning
confidence: 98%
“…Boron doped ZnO for use in DSSC synthesized via solegel technique has been reported in Ref. [19]. In this work, we have introduced a new technique of boron doping into ZnO nanotubes that is adding H 3 BO 3 in a growth solution containing Zn(NO 3 ) 2 and HMT.…”
Section: Introductionmentioning
confidence: 98%
“…Zinc oxide is a n-type semiconductor, crystallizes in a hexagonal wurtzite structure, with space group C 6 4v and lattice parameters; a = 3.25Å, c = 5.21Å [5]. Due to wide direct optical band gap ( 3.37 eV) at room temperature, high transmission coefficient in the visible and near infrared spectral range, large exciton binding energy of 60 meV at room temperature, zinc oxide (ZnO) is considered to be one of the most important multifunctional semiconductor material for technological applications such as transparent field effect transistors, light emitting diodes, gas sensors, window layer for thin-film solar cells, transparent conducting electrodes, surface acoustic wave devices, piezoelectric devices, drug delivery, photodiodes and optoelectronic devices such as ultraviolet (UV) light-emitting diodes (LEDs) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. ZnO is also biodegradable, biocompatible and biosafe for medical and environmental applications.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer dye A capped ZnO nanoparticles were further washed with excess of methanol and dried under vacuum. Polymer dye A capped ZnO nanoparticles were characterized using DLS, SEM, and solid state XRD [28].…”
Section: Preparation Of Polymer Dye a Capped Zno Nanoparticlesmentioning
confidence: 99%
“…In case of hybrid solar cell materials, more improvements in efficiency can be expected. Kumar et al [28] reported the efficiencies up to 1.56% and 1.84% for boron and aluminum doped ZnO based DSSCs, respectively. There are many fabrication techniques for ZnO based hybrid DSSCs including wet precipitation, thin film deposition method, spray coating, spin coating, solgel method, screen printing, chemical vapor deposition, and hydrothermal technique [10,12].…”
Section: Introductionmentioning
confidence: 99%